The association between hypogonadism symptoms with serum testosterone, FSH and LH in men. (2nd January 2018) - Samipoor, Forough; Pakseresht, Sedigheh; Rezasoltani, Parvaneh; Mehrdad, Mojtaba
Abstract: Objectives: This study aimed to determine the relationship of hypogonadism symptoms with the levels of sex hormones in men. Methods: This cross-sectional study was conducted on 140 men aged above 40 years. Data collections were conducted by Aging Male Scales (AMS) questionnaire and some sociodemographic variables. Then, 3 ml blood serum was sampled for testosterone (free and total), FSH and LH. Data were analyzed by descriptive and analytical statistics. Results: Mean age score was 52.09 ± 7.096. There was no significant association between total score of the symptoms of hypogonadism and serum total and free testosterone level while it was shown significant association with BMI ( p  = .021) and occupation ( p  = .005). Conclusion: The most men experienced the symptoms of hypogonadism and the majority of the symptoms were related to psychological domain. The symptoms of hypogonadism are considered to some factors like BMI and occupation too.